The impact of technology on Brazil’s Military Police: Operational efficiency and transparency in public security (Research, Society and Development, 2026)
Brazilian public security operates in a context of increasing institutional complexity, in which changes in criminal dynamics, demands for state efficiency, and the requirement for transparency impose new challenges. In this context, the incorporation of technologies into Military Police institutions enables the improvement of operational processes, the strengthening of planning capacity, and the enhancement of control and accountability mechanisms. The general objective of this study is to analyze the impacts of the use of technological tools in the Military Police forces of Brazil, with emphasis on operational efficiency and institutional transparency. To this end, the research adopts a qualitative approach, of an applied nature, with descriptive-analytical objectives, based on an interdisciplinary literature review and documentary analysis of institutional reports and national and international academic studies. The results indicate that the implementation of body-worn cameras contributes to reducing conflicts between police officers and citizens, increases social trust in the police institution, and reinforces the legal security of officers on duty. It is concluded that the adoption of this technology should be understood as a strategic investment by the Military Police, promoting efficiency, transparency, and professional recognition, in line with the contemporary demands of a democratic society.